Diagnostic accuracy of FeNO in asthma and predictive value for inhaled corticosteroid responsiveness: A prospective, multicentre study. (August 2022) - Schneider, Antonius; Brunn, Benjamin; Hapfelmeier, Alexander; Schultz, Konrad; Kellerer, Christina; Jörres, Rudolf A.
Summary: Background: Fractional exhaled nitric oxide (FeNO) is promising for diagnosing asthma and could replace bronchial provocation (BP). To date, cut-off values have been derived by post hoc analysis only. The aim was to validate the diagnostic accuracy for predefined FeNO cut-off values and the predictive value for responsiveness to inhaled corticosteroids (ICS). Methods: We conducted a prospective, diagnostic, multicentre study with patients attending three private practices of pneumologists in Upper Bavaria, Germany, from July 3, 2020 to Jan 21, 2022. Index test was FENO measurement. Reference standard was Tiffeneau ratio (FEV1 /VC) or airway resistance as assessed by whole body plethysmography, with additional BP or bronchodilation test. Follow-up was performed after 12 weeks. Analyses of Receiver Operating Characteristics curves were conducted to determine the diagnostic accuracy and predictive value of FeNO. Findings: 308 patients with complete follow-up were recruited, 186 (60·4%) were female, average age was 44·7 years, 161 (52·3%) had asthma. Regarding diagnostic accuracy, the area under the curve (AUC) was 0·718 (95% CI 0·661–0·775; p < 0·001). Sensitivity at FeNO >50 ppb was 0·24 (95% CI 0·18–0·32), specificity 0·99 (0·95–1·0), positive predictive value (PPV) 0·95 (0·84–0·99), negative predictive value (NPV) 0·54 (0·48–0·60). In 66 patients with ´wheezing´ and ´allergic rhinitis´, the sensitivity at FeNO >33 ppb was 0·49 (0·34–0·64), specificity 0·88 (0·64–0·99), PPV 0·92 (0·75–0·99), NPV 0·38 (0·23–0·54). In 68 patients with ICS medication, responsiveness was predicted at the cut-off >43 ppb, with a sensitivity of 0·55 (95%CI 0·36–0·74), specificity 0·82 (0·66–0·92), PPV 0·70 (0·47–0·87), NPV 0·71 (0·56–0·84). Interpretation: FeNO measurement allows a valid ruling-in of an asthma diagnosis, whereas ruling-out of asthma is not possible. Enhanced probability of ICS responsiveness is also given with increased FeNO values. Funding: Circassia Germany gave 25% discount on the purchase of three NIOX VERO devices.